Encephalopathy related to Status Epilepticus during slow Sleep: a link with sleep homeostasis?. (18th May 2020) - Rubboli, Guido; Huber, Reto; Tononi, Giulio; Tassinari, Carlo Alberto
Abstract: Encephalopathy related to Status Epilepticus during slow Sleep (ESES) is a childhood epilepsy syndrome characterized by appearance of cognitive and behavioural disturbances in conjunction with a striking activation of EEG epileptic abnormalities during sleep. The link between the extreme amount of epileptic discharges during sleep and the deterioration of cognitive functions and behavior is poorly understood. We hypothesize that the negative effects of ESES may depend on the impairment of the synaptic homeostasis processes occurring during normal sleep and that are particularly important in the developmental age. Sleep ensures synaptic homeostasis by promoting synaptic weakening/elimination after the increase of synaptic strength that occurs during wakefulness. Changes in synaptic strength are reflected in the EEG by changes of sleep slow wave activity (SWA). Recent studies in ESES have failed to show changes of sleep SWA, particularly at the site of the epileptic focus, suggesting a spike‐related impairment of the homeostatic recovery of sleep. This impaired synaptic homeostasis in the critical period of development may alter cortical wiring and thereby disrupt, often irreversibly, cognitive functions and behavior, leading to the neuropsychological compromise typical of ESES.